Shared Perceptions of Fatigue Management in Workgroups: A Cross-Level Moderator of the Negative Impact of Work Spillover on Custodial Officer Outcomes. (April 2023) - Way, Kïrsten A.; Jimmieson, Nerina L.; Manchha, Asmita; D'allura, Louise
Custodial officers perform unique and challenging work tasks making it a profession with predictable work-to-home spillover. Drawing on Spillover and Safety Climate theories, we hypothesized that work-to-home spillover would be associated with higher psychological distress, sleep disturbance, binge drinking, and commuting incidents, and that these individual-level effects would be buffered in workgroups with a shared perception that fatigue was managed well. Using a mixed-methods design, multilevel quantitative data (498 employees nested in 72 workgroups across 12 Australian prisons) and qualitative data (from 63 structured interviews) were collected. Results supported predicted main effects for psychological distress, sleep disturbance, and commuting incidents, and a cross-level buffering effect on the positive relationship between custodial work spillover and psychological distress that occurs when workgroups perceive their organization is managing fatigue well. We found qualitative support for relationships via the emergence of six themes including how custodial officers experience a collective sense of fatigue management.